أسبقية الفكر الإسلامي في قضية العيش المشترك مقاربة فلسفية في فكر أبي الريحان البيروني (Journal of Humanitarian and Applied Sciences, 2023)
This study aimed to confirm that the issue of coexistence has well-established roots in the thought of Abi Al-Rayhan Al-Biruni. What Al-Biruni came up with about addressing this issue is very similar to philosophers and thinkers from the modern era and contemporary thought. The researcher used the analytical approach and the historical approach, and concluded that the philosophical approach to the idea of ​​coexistence has been achieved to a large extent, as Al-Biruni had put forward the principles of the idea of ​​coexistence that came to Western philosophers.
Keywords: The idea of ​​coexistence; acceptance of the other; difference; respect for freedoms; comparison of religions; confirmation of similarity